KAJIAN PEKERJA PEREMPUAN PADA PERUSAHAAN PERKEBUN KELAPA SAWIT DI DISTRIK KLASAFET KABUPATEN SORONG (STUDI KASUS: PT. HENRISON INTI PERSADA) (The Study of Women Workers at Palm Oil Plantation Companies in Klasafet Sub District Sorong Regency (Case Study: PT. Henrison Inti Persada)) - Diana Naa; Theodora M. Katiandagho; Eyverson Ruauw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is to determine the characteristics of female workers and how much income  received in oil palm plantation This research has been conducted for 3 months from June to August 2018 at  PT Henrison Inti Persada, located in the Klasafet  District, Sorong Regency. The sampling method uses the Purposive sampling method. The type of data used is primary data and secondary data. Primary data collection is done by interviewi ng respondents directly and using a list of questions that have been prepared, female labor respondents as monthly employees in the company. Secondary data were obtained from the agencies or institutions involved in this study, such as the Office of the Oil Palm Plantation Company PT. HIP          The research results showed that young non-local female workers aged 23-40 years were 9 people (60%), local female workers with an elementary school education of 10 people (66.67%) and the marital status of married female workers and the number of dependents for more families between 1-5 9 people (60%). The duration of Non-local female workers from 4-10 years is 12 people (80%) and the Field of Work in PT HIP as a palm oil keeper, Non-local female workers who do not have other jobs and only work at PT HIP totaling 12 people (80%) Local female jobs have 6 other jobs (40%), Origin of the workforce comes from East Nusa Tenggara with 11 people (36.67%) and West Papua which is 15 people (50%), Non-local female workers total 12 as many as (80%) people who claimed to work as laborers at PT HIP wanted to increase family income and to support family economic stability. The working hours set by PT HIP for all oil palm workers in PT. HIP Sorong Regency for one day, which is 8 hour,  start working from 06.00  to 14.00 o’clock and the highest wage of female workers at PT HIP per month was Rp. 2,301,000 to Rp. 2,500,000 with a total of 19 people (63.33%).Keywords: Women Workers, PT. Hendrison Inti Persada, Sorong Regency, West Papua